Stunting prevention efforts in Siyangan Village, Tegalrejo District, Magelang - Robiul Fitri Masithoh; Dini Rahmah Fitriyani; Amelia Saputri; Khoirul Fahmi Alkharis; Rama Ramadhani; Andhika Seno Aji (Universitas Muhammadiyah Magelang, 2023)
A child is considered stunted if, by the time they turn two years old, both his height and body length are below the WHO Multicentre Growth Reference Study standard. The aim of this PPMT activity is to increase public awareness and knowledge about stunting and improve food security. This program uses PRA, a strategy that includes socialization, training, and assistance with food security to improve the health of children with stunting. the general public's knowledge of stunting and efforts to prevent it has grown. By utilizing local resources, the team also hopes to assist the community increase its food security.